2022
DOI: 10.1155/2022/3610461
|View full text |Cite|
|
Sign up to set email alerts
|

Progress of Research on the Application of Triple Antibiotic Paste and Hydrogel Scaffold Materials in Endodontic Revascularization: A Systematic Review

Abstract: Objective. To evaluate the application of hydrogel scaffold materials and triple antibiotic paste in endodontic regeneration through literature review. Methods. An electronic search of the literature published on PubMed, Wangfang database, and CNKI database using the search terms “endodontic regeneration,” “pulp blood flow reconstruction,” “recanalization,” “triple antibiotic paste,” and “scaffold material” was conducted. The searched literature was used for analysis. Results and Conclusion. Hydrogels regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%